Implications of EU environmental policies on agriculture in Europe and beyond (2022)
The European Union is taking several policy initiatives to combat climate change and the loss of biodiversity with direct impact on agriculture. For farmers the European Commission is promoting an instrument called OECM, Other effective area-based conservation measures. Other effective area-based conservation measures (OECMs) are a new conservation approach, separate from protected areas, where conservation is achieved mainly as a by-product of other management. OECMs can be counted towards the EU target if: i) Conservation objectives and measures are in place; ii) the area is covered by a national or international legal or administrative act or a contractual arrangement achieving long-term conservation outcomes and iii) effective management and monitoring of the biodiversity in the area is in place. A new growth strategy that aims to transform the EU into a fair and prosperous society with a modern, resource-efficient and competitive economy where there are no net emissions of greenhouse gases in 2050 and where economic growth is decoupled from resource use. While those initiatives mainly impact the life and work of European farmers, there is as well an indirect impact to farmers elsewhere in the world